Analysis of Factors Affecting Economic Growth in Mamuju Regency, West Sulawesi - Rizaldi, Muhammad Alfian; Heryati, Yati; Sahputra, Jeffriansyah Dwi (Jurnal Economic Resource, 2024)
This research is titled The Influence of Population Growth, Employment Budget and Investment on Economic Growth in Mamuju Regency. The types of data used in this study are qualitative and quantitative. The data sources used in this study are secondary data and primary data. This study uses multiple linear regression analysis to calculate the quantitative impact of each factor on the change in event (factor X) and then statistical tests are carried out. The results of the study showed that the Population Growth factor with a significant value of 0.029< 0.05 and the Labor Force factor with a significant value of 0.033< 0.05, and the Investment factor with a significant value of 0.039 < 0.05. The results of the simultaneous test showed a Fcal value of 22.364> Ftable 6.256 with a significant level of 0.35. Thus, it can be stated that Population Growth, Restaurants and Entertainment simultaneously have a significant effect on Economic Growth in Mamuju Regency. And the most dominant Population Growth Factor has an effect on Economic Growth in Mamuju Regency with the highest beta value of 5.636 with the lowest significant level of 0.029, when compared to the beta value of other factors.